2013
DOI: 10.4103/0973-6131.105945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the integrated approach of yoga therapy on platelet count and uric acid in pregnancy: A multicenter stratified randomized single-blind study

Abstract: Background:Yoga improves maternal and fetal outcomes in pregnancy. Platelet Count and Uric acid (Ua) are valuable screening measures in high-risk pregnancy.Aim:To examine the effect of yoga on platelet counts and serum Ua in high-risk pregnancy.Materials and Methods:This stratified randomized controlled trial, conducted by S-VYASA University at St. John's Medical College Hospital and Gunasheela Maternity Hospital, recruited 68 women with high-risk pregnancy (30 yoga and 38 controls) in the twelfth week of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…reported prenatal yoga as an effective technique for reducing gestational hypertension and preeclampsia. [45] Leeners et al . found that mental stress during pregnancy was associated with a 1.6-fold increase in the risk of gestational hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…reported prenatal yoga as an effective technique for reducing gestational hypertension and preeclampsia. [45] Leeners et al . found that mental stress during pregnancy was associated with a 1.6-fold increase in the risk of gestational hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies with healthy, non-depressed samples suggest that yoga may improve overall maternal health and wellbeing, as it is associated with lower lumbo-pelvic pain (Martins & Pinto, 2013), better quality of life (Rakhshani, Maharana, Raghuram, Nagendra, & Venkatram, 2010), lower stress (Satyapriya, Nagendra, Nagarathna, & Padmalatha, 2009), and decreased delivery pain (Chuntharapat, Petpichetchian, & Hatthakit, 2008). Further, women with high risk pregnancies who practiced yoga are less likely to develop pregnancy-induced hypertension or pre-eclampsia (Jayashree et al, 2013), and had fewer preterm births (Rakhshani et al, 2012). However, no studies to date have evaluated pregnancy and birth outcomes among depressed women practicing yoga.…”
Section: Discussionmentioning
confidence: 99%
“…Being over 5000 years old, the science of yoga has been shown to impact a variety of physical and psychological health conditions, including anxiety, depression, metabolic syndrome, cancer, and cardiovascular, musculoskeletal, and pulmonary disorders [ 9 , 10 ]. Additionally, yoga has been shown to improve the outcomes in low-risk [ 11 ] and high-risk pregnancies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%